2020
DOI: 10.1038/s41598-020-62660-1
|View full text |Cite
|
Sign up to set email alerts
|

Species identity and diversity effects on invasion resistance of tropical freshwater plant communities

Abstract: Biotic resistance mediated by native plant diversity has long been hypothesized to reduce the success of invading plant species in terrestrial systems in temperate regions. However, still little is known about the mechanisms driving invasion patterns in other biomes or latitudes. We help to fill this gap by investigating how native plant community presence and diversity, and the presence of native phylogenetically closely related species to an invader, would affect invader Hydrilla verticillata establishment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Petruzzella et al. (2020) reported that mature and undisturbed native plant communities with rich plant diversity (as was observed at the uninvaded treatment) provide greater resistance to alien plant invasion. More research is required to investigate why some ecosystems are resistant to alien plant invasion.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Petruzzella et al. (2020) reported that mature and undisturbed native plant communities with rich plant diversity (as was observed at the uninvaded treatment) provide greater resistance to alien plant invasion. More research is required to investigate why some ecosystems are resistant to alien plant invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Several invasion resistance factors can explain why E. grandis species were not present in the uninvaded sites. Such factors include (a) resistance of native ecosystem to plant invasion due to biotic resistance mediated by high plant diversity, and (b) allelopathic effects of some native species (Dutt, 2018; Petruzzella et al., 2020). Petruzzella et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biotic resistance hypothesis asserts that communities which are more diverse are less susceptible to biological invasions than less diverse communities [23,24]. The riparian habitats dominated by I. glandulifera are prone to invasives, in part due to their high disturbance regimes [25].…”
Section: Lesson Number One: Impatiens Glandulifera Has a Differential...mentioning
confidence: 99%